A proposed additional property to the Weyuker's existing properties. (18th January 2006) - Misra, Sanjay; Misra, A.K.
The existing Weyuker's properties as they stand do not account for the programming language. So there is a need to add more properties to the list, which will address the language of a program. If we compute the same function in a different language, the complexity of the program should be the same, a concern which is not yet addressed by any of the existing Weyuker properties. For this purpose a new property to tackle this problem is proposed. This paper attempts to establish this property as useful in evaluating the complexity of a program.